Diseño de un proceso para la mejora del cambio de guaya en el sistema corte de la unidad de Ccquización retardada de la Refinería de Cartagena S.A.S. (2023)
In the present degree work, the design of a process for the improvement of the change of wire in the cutting system of the Delayed Coking unit of the Refinería de Cartagena S.A.S. To achieve this objective, firstly, an analysis of the current way in which the process was carried out in the company was carried out. Which turned out to be complex, high risk, with high execution times and with the intervention of a large number of workers. And, thanks to the application of the Ishikawa tool, it was found that the main cause of these symptoms was the absence of a defined method for carrying out the change of the wire. Subsequently, three alternatives for improvement were proposed and evaluated, of which the execution of the wire rope change with cable grip + mechanical winch was selected due to the reduction in time, number of workers and the automatic mode of action that made it safer for the personnel. equipment and process in general. These being two hours and three workers respectively.